Unraveling Errors in Poetry: A Translation Quality Assessment of Sapardi Djoko Damono's Sajak Orang Gila - Firdausi, Annisa Nurul; Setiawan, Teguh; Jati, Dindadari Arum; Rahmi, Hafizatur (LingTera, 2025)
Poem translation is challenging. It must bridge not only equivalence and cultural aspects, but also the acceptability of the poem. The translated product needs to be evaluated to determine whether the translation is acceptable. This study aims to investigate the Translation Quality Assessment (TQA) of an Indonesian poem titled Sajak Orang Gila by Sapardi Djoko Damono and its translation Ballad of a Crazy Man by John H. McGlynn. While translating poetry, some errors are inevitable. However, by applying TQA, such mistakes can be identified and addressed for future improvement. This study employed a qualitative-descriptive method and used Juliane House’s (1997) theory of TQA. The results showed that the translator applied domestication and literal translation in his work. The translator attempted to maintain close alignment between the source text (ST) and target text (TT). The errors identified were overt errors, which include several categories: untranslated segments, slight changes in meaning, significant changes in meaning, breach of the SL system, creative translation, and cultural filtering. However, distortion of meaning was not found in this research. This indicates that the translator successfully translated the poem.